BUSINESS PLAN CAFE LUDOS - Ishak Hendradiarta Gunawan (Perpustakaan Universitas Surabaya, 2014)
The journal aims to evaluate all aspects of the business feasibility of Cafe Ludos. The changes from technology era to the era of conceptual, required humans to be able to think creatively, so that his position is not replaceable by machines. There is a study which stated that work in the coffee shop, can increase the creativity to be able to think out of the box. Cafe Ludos is a coffee shop that uses a vintage atmosphere, which old-fashioned feel of a classic yet elegant. Based on the results of this feasibility study business plan to get good results with the results of the NPV is Rp. 471 037 879, - with an IRR of 41.03%. While the payback period is 2 years and 5 months. Based on these results it can be said this business feasible.